Anticancer Activity and Safety Profile of Novel 1-(4-Fluorophenoxyacetyl)-4-substituted Thio/Semicarbazide Derivatives - Paweł Kozyra; Ewelina Humeniuk; Zbigniew Karczmarzyk; Adrian Borzęcki; Grzegorz Adamczuk; Agnieszka Korga-Plewko; Waldemar Wysocki; Monika Pitucha (Molecules)
Compounds with thiosemicarbazide and semicarbazide scaffolds are among the most promising structures in medicinal chemistry due to the possibility of forming multiple hydrogen bonds. Therefore, six new derivatives of 4-fluorophenoxyacetylthiosemicarbazide and 4-fluorophenoxyacetylthiosemicarbazide were designed to compare their physicochemical properties, biological activity, and in silico pharmacokinetic parameters. All compounds were characterized by 1H, 13C NMR, 19F, IR spectra. For selected derivatives (AB2 and AB5), X-ray studies were performed to confirm their synthetic route and identify the tautomeric forms and intra- and intermolecular interactions occurring in the crystalline state. In the in silico pharmacokinetic study, a clear difference in lipophilicity was observed between thiosemicarbazide and semicarbazide derivatives. In vitro biological studies have shown the promising activity of thiosemicarbazides against prostate cancer cell line LNCaP, with a higher safety profile than semicarbazides. The most active compound AB2 showed IC50 = 108.14 μM against LNCaP. Based on biological studies, topoisomerase IIα was proposed as a potential molecular target, which was confirmed by molecular docking studies.